2021
DOI: 10.1007/s00586-021-07001-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cauda equina syndrome due to lumbar disc herniation after surgical management and the factors affecting it: a systematic review and meta-analysis of 22 studies with 852 cases

Abstract: Purpose This study aimed to investigate the long-term clinical outcomes after surgical decompression in cauda equina syndrome (CES) and see if any preoperative patient-related factors contributed to this outcome. Methods A systematic literature search was conducted in the electronic databases of PubMed, Embase, Scopus, and Ovid. Data regarding outcome parameters from eligible studies were extracted. Meta-analysis was performed using a randomeffect model. Results A total of 852 patients (492 males and 360 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Studies have consistently demonstrated that the duration of nerve compression is inversely related to the recovery of motor, sensory, and autonomic functions. In this case, surgical intervention was within the window period typically advocated for optimal outcomes, generally within 48 h of symptom onset [ 19 ]. The early release of cauda equina compression likely contributed to the progressive recovery of her neurological function, as evidenced by the return of independent ambulation and improvement in bladder and bowel control over two years.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have consistently demonstrated that the duration of nerve compression is inversely related to the recovery of motor, sensory, and autonomic functions. In this case, surgical intervention was within the window period typically advocated for optimal outcomes, generally within 48 h of symptom onset [ 19 ]. The early release of cauda equina compression likely contributed to the progressive recovery of her neurological function, as evidenced by the return of independent ambulation and improvement in bladder and bowel control over two years.…”
Section: Discussionmentioning
confidence: 99%
“…Since no difference has been shown in outcomes between operating in the first 24 hours versus between 24 and 48 hours, it may be reasonable to briefly delay surgery for CES patients under specific circumstances where preoperative factors can be feasibly optimized [ 10 , 26 , 27 ]. Additionally, operating outside normal operating room hours (e.g., during nighttime) has been shown to be an independent risk factor for complications in spine surgery performed for CES [ 28 , 29 , 30 ]. Preoperative optimization may help equilibrate outcomes after lumbar decompression performed in the setting of CES closer to those of lumbar decompression performed electively.…”
Section: Discussionmentioning
confidence: 99%
“…Calcified lumbar disc herniation (CLDH) 1 is a complex type of disc herniation that is complicated by disc calcification or osteophyte formation on the basis of lumbar disc herniation. Because calcified tissue often adheres to nerve roots or the dura mater, the difficulty of surgery increases and can easily lead to complications such as nerve damage, dural damage, and cerebrospinal fluid leakage.…”
Section: Introductionmentioning
confidence: 99%